Delamination mechanism of thermal barrier coatings induced by thermal cycling and growth stresses. (March 2021) - Xiao, Y.Q.; Yang, L.; Zhu, W.; Zhou, Y.C.; Pi, Z.P.; Wei, Y.G.
Highlights: A damage phase field based FEM model considering thermal cycling and growth stresses is developed. The interaction between the thermal cycling and growth stresses accelerates TBCs damage. The delamination mechanisms of TBCs under different interface roughness are obtained. Abstract: The growth of thermally grown oxide (TGO) is often regarded as a key factor causing failures of thermal barrier coatings (TBCs) because it leads to thermal cycling and growth stresses. However, the delamination mechanism of TBCs induced by the growth process of TGO is still unclear. Here, a finite element method (FEM) considering both thermal cycling and growth stresses is developed. The accumulation of damage and crack nucleation, propagation, and coalescence are obtained using a phase field damage model. The results indicate that there is a critical TGO thickness of 8–10 μm, which may result in delamination of the TBCs. Both thermal cycling and growth stresses induce the premature failure of TBCs. The delamination mechanism induced by thermal cycling and growth stresses is obtained. When the interface roughness is A / L ≥ 1/4, the cracks pass through the TGO/TC interface and propagate in the TC layer. When the interface roughness is A / L ≤ 1/8, the cracks propagate along the vicinity of the TGO and will not pass through the TC/TGO interface. When the interface roughness is 1/8 < A / L less than 1/4, the cracks bifurcate at the vicinity of TGO interface, and one branch propagates in the TC and the other propagates along the vicinity of the TGO.